Facilitated access to Iranian patent information - Bagheri, Seyed Kamran (World patent information, 2014)
Until recently, the published patent information from the Iranian Patent Office was rather limited. There were no open-to-public databases or gazettes for Iranian patents. The only official statistics available on Iranian patents were the number of filed applications and granted patents in each year, published by the national Patent Office. Lately, however, there has been major progress as the Office has launched its first ever on-line searchable patent database. This paper gives a general overview of patent disclosure as specified in Iranian patent law and regulations. It then describes what used to be the only way to access patent bibliographic data in Iran. Next, it highlights the new promising initiative and introduces the new online database of the Iranian Patent Office and its search features. Finally, the paper looks at some recent policy initiatives and argues that the Iranian Patent Office is about to experience a major transition to a more efficient organization. Inter alia, this could pave the way for improved and timely access to accurate information on the patents registered in the country. •Improvements to information availability for Iranian patents are discussed.•Related developments in the patent laws of Iran, eg on patent disclosure, reviewed.•Functionality of trial Iranian patent information database described.